Interfade Duration Statistics at Ku-band for Satellite Earth Links System in Equatorial Malaysia: Modeling Distribution - Mawarni Mohamed Yunus; Jafri Din; Siat Ling Jong (Universitas Ahmad Dahlan, 2017)
Fade dynamics is one of more important parameters when implementing Fade Mitigation Techniques (FMTs) to counteract an excessive attenuation that affect satellite communication systems operating above 10 GHz. The statistics of probable duration between two rain fade namely interfade duration enables system operator to estimate how long the system will need to recover before the next outage and assist in designing the FMTs. In this paper, interfade duration statistics have been derived from one year of slant path attenuation measurements data collected in Equatorial Johor Bahru at 12.2 GHz with elevation angle of 75.61o. The result had shown the dependency of number of events with attenuation thresholds. Empirical interfade duration statistics are also obtained and suitable model distribution are proposed.